Testing the efect of an integrated-intervention to promote access to sexual and reproductive healthcare and rights among women with disabilities in Ghana: a quasi-experimental study protocol - Ganle, J.K.; Ofori, C.; Dery, S. (Ganle et al. Reprod Health, 2021)
.Abstract Background: There is evidence that women with disabilities (WWDs) experience the most difficulty accessing and using sexual and reproductive health and rights (SRHRs) services and information worldwide. However, there are cur rently no workable interventions to reach WWDs with essential SRHR services. This study aims to test the efect of an integrated health facility and individual-level intervention on access to SRHRs information and services among sexu ally active WWDs aged 15–49 years in Ghana. Methods: A quasi-experimental study design with four arms will be implemented in four districts in the Northern region of Ghana to test the efect of three inter-related interventions. The inventions are (1) capacity building in disability-centred SRHRs information and service delivery for healthcare providers, (2) support for WWDs to access disability-unfriendly healthcare infrastructure, and (3) one-on-one regular SRHRs education, information provision, and referral. The frst two interventions are at the health-facility level while the third one is at the individual/family level. The frst arm of the experiment will expose eligible WWDs to all three interventions. In the second arm, WWDs will be exposed to only the two-health facility-level interventions. The third arm will expose WWDs to only the individual level intervention. The forth arm will constitute the control group. A total of 680 (170 in each arm) sexually active women with physical disability and visual impairments will take part in the study over a period of 12 months. To assess the efect of the interventions on key study outcomes (i.e. awareness about, and use of modern contraceptive, ANC attendance, and skilled delivery among parous women), pre- and post-intervention surveys will be conducted. Diference-in-Diference analysis will be used to examine the efect of each intervention in comparison to the control group, while controlling for confounders. Cost-efectiveness analyses will also be conducted on the three-intervention arms vis a vis changes in key outcome measures to identify which of the three interventions is likely to yield greater impact with lower costs. Discussion: Lack of access to SRHRs information and services for WWDs is not only a violation of their right to appro priate and quality SRH care but could also undermine eforts to achieve equitable health under SDG 3. This research is expected to generate evidence to inform local health programmes to increase access to SRHRs among WWDs by strengthening local health system capacity to provide disability-sensitive SRHRs services.
Research Article
Keywords: Disability; Women with disability; Reproductive health; sexual health; Rights; Access; Ghana